J.T. LeRoy [videorecording (DVD)] - Kelly, Justin (Director); Stewart, Kristen, 1990-; Kruger, Diane, 1976-; Dern, Laura; Knoop, Savannah (Universal Pictures Home Entertainment, 2019)
Based on Savannah Knoop's memoir Girl Boy Girl: How I Became JT LeRoy, this captivating true story goes beyond the headlines to tell the story of the most compelling literary hoax of recent times. Laura Albert writes as her avatar, 'a disenfranchised young queer man' named JT LeRoy. When her debut novel becomes a best-seller and JT becomes the darling of the literary world, she comes up with a unique solution to preserve her anonymity but give life to her nom-de-plume.